Education on the manufacture of personal protective equipment as a prevention of covid-19 infection in farmer women's groups in Bulu Village, Magelang - Sumarno Adi Subrata; Citra Resti; Verenina Chandra Maulidia; Arifah Rahmawati; Rahma Fanisa; Laila Tastaftyani Ningrum (Universitas Muhammadiyah Magelang, 2021)
The female farmer has multiple roles in their daily lives. Apart from this, they also have to do other housework. Unfortunately, this condition makes them have less attention to their health. Therefore, during the current covid-19 pandemic, the group of females needs to optimize their role particularly involving them in particular activities focusing on the prevention of covid-19 infection. Therefore, this activity aims to improve the ability of female farmer groups in making personal protective equipment. This activity was carried out during June 2021 in Bulu Village, Kapuhan, Sawangan, Magelang Regency. The results of this activity indicate that the female farmers' group can make personal protective equipment. It is hoped that the result of this activity can be widely used in the village. When possible, that product can be sold to increase the economic growth in the village.